(3MGdI CReI YGe (B2008s - (3ScjfI(B, (3Hf MehOs ((3GdLRGFQ(B:s (3OGQ GdMOjK ddcJGH(B,s, 2014)
(3jJfGhd gPG GdcJGH CSS hOYGFe GdfXGe GdQCSeGdj HOGjI HGdCfXeI GdGbJUGOjI Ke GdJjGQGJ GdCSGSjI GdJj SGgeJ aj HdhQI Yde GdGbJUGO, eY GdGTGQI Edi PcQ fXGe GdMQjI GdGbJUGOjI GdJj jQcR YdjgG Yed GdfXGe GdQCSeGdj(B. (3ceG Cfg jJYQV Edi OQGSI GdCReGJ GdJj eQ HgG GdfXGe GdQCSeGdj HOGjI HGdCReI GdGbJUGOjI GdcHQi heG JdJgG ef CReGJ GdbQf GdYTQjf, gPg GdCReGJ dGbJ GdcKjQ ef GdJaSjQ GdfXQj hGdCcGOjej HOGjI HJaSjQ cjfR Ke JaSjQ GdfbOjjf hJaSjQ ZjQ GdfbOjjf(B.(3ceG jJYQV gPG GdYed Edi OQGSI eSJajVI ddCReI GdeGdjI GdYGdejI dSfI (B2008.s
(3eQGLY U(B.192s
Keywords: (3GdCReGJ GdeGdjIs; (3GdQCSeGdjIs